Model of Culture of Future Economists Business Communication - Victoria Budianskaya (Pedagogical Discourse, 2012)
The bases of forming the model of culture of business communication of students in the process of their professional training are considered in the article. The term „culture” is analyzed taking into account different approaches – linguistic, psychological, pedagogical and social. The bases of culture of communication are analyzed in the work, the basis of culture of business communication is considered and analyzed, the components of model of culture of business communication of students are outlined: motivational and valued, linguistic and informative, operational and active. The specifics of forming the culture of business communication in economic institutes is outlined: students must study to explain certain economic phenomena correctly, work with business correspondence, conduct future business negotiations, sign contracts etc